Dignity and Selective Self‑Presentation - Matheson, David (Lessons from the identity trail: anonymity, privacy and identity in a networked society, 2009)
"During the past decade, rapid developments in information and communications technology have transformed key social, commercial, and political realities. Within that same time period, working at something less than Internet speed, much of the academic and policy debate arising from these new and emerging technologies has been fragmented. There have been few examples of interdisciplinary dialogue about the importance and impact of anonymity and privacy in a networked society. Lessons from the Identity Trail: Anonymity, Privacy and Identity in a Networked Society fills that gap, and examines key questions about anonymity, privacy, and identity in an environment that increasingly automates the collection of personal information and relies upon surveillance to promote private and public sector goals." "This book has been informed by the results of a multi-million dollar research project that has brought together a distinguished array of philosophers, ethicists, feminists, cognitive scientists, lawyers, cryptographers, engineers, policy analysts, government policy makers, and privacy experts. Working collaboratively over a four-year period and participating in an iterative process designed to maximize the potential for interdisciplinary discussion and feedback through a series of workshops and peer review, the authors have integrated crucial public policy themes with the most recent research outcomes."--BOOK JACKET.